Gender-Specific Differences in Depressive Behavior Among Forensic Psychiatric Patients - Streb, Judith; Ruppel, Elena; Möller-Leimkühler, Anne-Maria; Büsselmann, Michael; Franke, Irina; Dudeck, Manuela (Frontiers in Psychology, 2021)
Background Women are almost twice as likely to develop depression than men, but men commit suicide more often. One explanation for this paradox is that current depression inventories do not fully capture typical male symptoms of depression. Several studies showed that most depression symptoms in men are masked by externalizing behaviors, such as aggressiveness, addiction, and risky behavior. Here, we explored the differences in depression symptoms between men and women in a forensic psychiatric sample. Methods We screened 182 forensic psychiatric patients and selected a matched sample (21 women and 21 men). External symptoms of depression were assessed with the Gender-Sensitive Depression Screening (GSDS) and internal symptoms with the Beck Depression Inventory Revision. Results Although externalizing behaviors were similar in both groups, we found a significant relationship between external and internal depression symptoms only in men. In addition, male forensic patients with a history of suicide had higher scores in the GSDS, whereas female patients with a history of suicide had higher scores in the Beck Depression Inventory Revision. Discussion The finding that the GSDS detected depression symptoms in men indicates that this instrument might be useful for developing assessments to prevent suicide in forensic practice.